Chloramination of iopamidol- and bromide-spiked waters containing natural organic matter - Nana Osei B. Ackerson (IWA Publishing, 2021)
Iopamidol (an iodinated X-ray contrast medium) and bromide are precursors in the formation of halogenated disinfection byproducts (DBPs). The interactions of these precursors are vital to elucidate the formation of halogenated DBPs during chloramination. This work investigated the formation of total organic halogen and select individual DBPs in two laboratory-chloraminated source waters containing iopamidol and bromide. Experiments were carried out in batch reactors containing Barberton source water (BSW) and Cleveland BSW (CSW), spiked with iopamidol (5 μM), bromide (15 μM), and 100 μM monochloramine. Total organic iodine concentrations were approximately equal regardless of source water since they are mostly unreacted iopamidol and iopamidol DBPs. Almost equal amounts of total organic chlorine (3–4 nM) were produced in the source waters, but higher quantities of total organic bromine were formed in BSW than CSW. Substantial quantities of regulated trihalomethanes (THMs) and haloacetic acids (HAAs) were formed in the source waters, along with appreciable concentrations of iodinated trihalomethanes (CHBrClI, CHCl2I, and CHBr2I). Low concentrations of iodo-HAAs were detected, especially at low pH. Overall, bromide concentrations appeared to suppress iodo-DBP formation during chloramination of iopamidol in the presence of natural organic matter. A good correlation (R2 = 0.801) between the yields of regulated DBPs and iodo-DBPs was observed. HIGHLIGHTS Bromide suppressed the formation of iodo-THMs without bromine atoms.; Approximately equal quantities of total organic chlorine were formed regardless of NOM characteristics.; Iodoacetic acids showed substantial formation at low pH irrespective of NOM.;